Melhoria de processo: a influ??ncia do desing thinking na qualidade percebida da gest??o de processos a partir da an??lise de indicadores de um pronto atendimento hospitalar na cidade de S??o Paulo - Botelho, Raphael (2020)
There is a tendency of innovation and competitiveness in the Health Sector that requires changes in management practices aiming improvements in organizational performance. This environment includes changes in customers profile, increased competition, the inclusion of new technologies, the search for efficiency in the application of resources and quality in operational performance. The investigation about the quality of service perceived by the client has been taking levels of complexity, addressing different marketing perspectives and refining feelings of experience. In other respects, emergency care units are compelled to increase the capacity of resolvability to overcome the challenges of patient safety and effectiveness of assistance in order to guarantee the sustainability of the market segment. The general objective of this work is to evaluate the quality perceived in the application of the Design Thinking method in emergency care services in the city of S??o Paulo. For this purpose, a Survey-type survey was applied, in the form of a closed structured questionnaire, with ditochromic questions, to measure the perceived quality of Process Management in hospital emergency services. The sampling plan was composed of a nonprobabilistic sample for convenience of 16 process owners service of an emergency hospital care. The findings showed that the knowledge about the management of the processes increased 120%. In other words: management was carried out in only 5 processes before the implementation; after the implementation of Design Thinking, management started to be carried out in 11 processes. The knowledge about the maintenance of processes increased by 225%, it means, the maintenance was done in only 4 processes and, after the implementation of Design Thinking, maintenance started to be carried out in 13 processes. The knowledge about the environment has a lower growth, at 18%. Before the environment was controlled in 11 processes, after the implementation of Design Thinking, the control started to be carried out in 13 processes. Finally, the understanding about customer orders grow 133%, it means, before customer requirements was just 6 processes; after the implementation of Design Thinking, the customer requirements started to be executed in 14 processes. This project - Design Thinking improved processes by 124% on average. This study contributed to health managers in emergency care to include in their management practice, the understanding of the Design Thinking methodology in service operations refer to the management, maintenance, environment and customer, enabling improvements policies, procedures, flows and indicators.